eWOM on Travel Agency Selection: Specialized versus Private Label - Bigné, Enrique and Caplliure, Eva‐María and Miquel, María‐José (Psychology & Marketing, 2016)
ABSTRACT In the travel industry, electronic word of mouth (eWOM) elicits a major influence on consumers’ decision making. Travel retailers are facing the new challenges derived from the different nature of their competitors—big hypermarkets, for instance, are extending their brands to travel services—and the challenges derived from online comments that consumers have access to. With a sample of 263 tourists, and using a fuzzy‐set qualitative comparative analysis data analysis, this paper shows how the selection between a specialized travel agency and a private label (PL) agency is influenced by five factors: the usefulness attached to online reviews by users and the valence of those online reviews, attitude and experience with PL, and the individual's value consciousness. The contribution of this paper not only comes from the novelty of considering PL in the context of travel agencies, but also from using a relatively novel data analysis approach useful for analyzing management issues.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTAwMi9tYXIuMjA5Mzg